From fitness to flourishing: culturally grounded implementation of the PERMAH model in Philippine physical education - Guinto, Maria Luisa M.; Campoamor-Olegario, Lizamarie A. (Frontiers in Psychology, 2025)
BackgroundDisruptions in education caused by natural disasters, conflict, or global crises pose significant challenges for educators, particularly in physical education (PE), where embodied learning and social interaction are essential. Following the COVID-19 pandemic, supporting the wellbeing of both students and teachers became a central focus of educational recovery. While the PERMAH model of wellbeing has garnered international attention, this study contributes to the growing body of work by exploring how it may take shape within culturally specific and resource-constrained educational contexts.MethodThis qualitative study examined how Filipino PE teachers implemented the PERMAH model—Positive Emotion, Engagement, Relationships, Meaning, Accomplishment, and Health—to support college students transitioning from online to in-person learning. Two focus group discussions were conducted with 13 instructors from a Philippine public university, all of whom taught parallel PERMAH and non-PERMAH PE classes. Reflexive thematic analysis was used to interpret participant narratives through the lens of Filipino psychology.ResultsFour key themes were generated: (1) creating meaningful connections, reflecting teachers' efforts to rebuild rapport and empathy with students; (2) nurturing safe spaces, demonstrating how they fostered emotional and physical safety in the classroom; (3) cultivating enjoyment and engagement, describe how they promote active participation and enthusiasm; and (4) enhancing teaching fulfillment, reveal how they developed their wellbeing and sense of professional purpose while incorporating PERMAH in their classes.ConclusionThis study presents one of the first culturally grounded applications of PERMAH in a Global South context. The findings suggest that locally adapted wellbeing frameworks, such as PERMAH, may help reframe PE as a more relational and meaningful space, offering insights that can inform curriculum design and educational reform.